THE USE OF RIGISCAN® EXAMINATION IN DIAGNOSING PATIENTS WITH ERECTILE DYSFUNCTION IN JAKARTA - Basukarno, Ari; Birowo, Ponco; Tri Prasetyo, Dimas; Rasyid, Nur (Indonesian Urological Association, 2018)
Objective: The aim of this study is to describe the characteristic of patients with Erectile Dysfunction (ED) and results of Nocturnal penile tumescence and rigidity (NPTR) based on Rigiscan® examination in patients with ED in Jakarta. Material & Methods: Descriptive-prospective study of patients with ED in Cipto Mangunkusumo Referral Hospital, Bunda General Hospital Jakarta, and ASRI-Siloam Urology Hospital are recorded during 2015. Patients’ age (in years), marital status (yes/no), duration of ED (in months), and International Index of Erectile Function-5 (IIEF-5) were recorded. NPTR examination were performed while patients were sleeping. Number of events, duration of each event (in minutes) as well as the rigidity (in percentage) and tumescence (in cm) were recorded. The elevation of tip and base penile circumference (in cm) during erection were also noted. Results: There were 34 patients who agreed to perform NPTR test. Most patients were married with the average age of 40.94 ± 10.81 years old. The duration of ED were varied from 5 to 96 months with average duration of 33.7 ± 44.34 months and IIEF-5 score was 6.38 ± 5.14. In general number of erections was 4 ± 3 with 23.4% of them had normal erection. The comparison between organic and psychogenic ED showed that the increment of circumference was significantly less in organic ED patients. Other parameters showed insignificant difference in statistical results. Conclusion: NPTR examination is an objective, effective, and easy-to-use measurement in order to differentiate between organic and psychogenic ED. One third of patients who complained with ED suffered from psychogenic ED and needed referral to other specialists.